If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -2m = 14 + 3m Solving 11 + -2m = 14 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 11 + -2m + -3m = 14 + 3m + -3m Combine like terms: -2m + -3m = -5m 11 + -5m = 14 + 3m + -3m Combine like terms: 3m + -3m = 0 11 + -5m = 14 + 0 11 + -5m = 14 Add '-11' to each side of the equation. 11 + -11 + -5m = 14 + -11 Combine like terms: 11 + -11 = 0 0 + -5m = 14 + -11 -5m = 14 + -11 Combine like terms: 14 + -11 = 3 -5m = 3 Divide each side by '-5'. m = -0.6 Simplifying m = -0.6
| (-4y^2-6y)+(5y^2+2y-5)= | | g(3)=x^2-3x | | 5x-2+2x=5x+x+7 | | 2a+2a+2a=56 | | 6n-10=2n+18 | | 146=l(20) | | (.5*x)*x=162 | | x-91=-7x+37 | | 0.15y=0.24 | | -3+4n=6n+3 | | 3z+20whenz=-8 | | 0.15=0.24 | | 156+125=180 | | .5x*x=162 | | 13x+1=y | | 0.5+3+125=180 | | 200=.5(10+x)4 | | 7x+15=4x-3 | | X+1.7=x | | K-1.06=5 | | 10x+10-15x=42 | | 6+4+x=21 | | 0.5+3=125 | | 4.6a-3.7=14.7 | | 221.606=-7.7(4.8x+5.3) | | R=12+5x | | 2a-5=3-a | | -20-6x=-4-3x | | 8-8k=10-7k | | 3x+4-9x+11= | | (-.75p)-2=.25p | | 7+2X+x=19 |